2018
DOI: 10.1177/1708538118799225
|View full text |Cite
|
Sign up to set email alerts
|

The different scenarios of urgent carotid revascularization for crescendo and single transient ischemic attack

Abstract: Objective Carotid stenosis with crescendo-transient-ischemic-attack (cTIA) requires a prompt intervention to reduce the stroke risk. Few data are reported in literature about cTIA suggesting a different perioperative risk compared with patients with single TIA (sTIA). This study aimed to compare the outcome of carotid endarterectomy (CEA) in patients with TIA (single/crescendo) and evaluate the outcome risk-factors. Methods Data from two tertiary hospitals for vascular treatment were analyzed from 2007 to 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
8
0
2
Order By: Relevance
“…A total of 624 records were identified from 5 databases and 19 studies were included for final quantitative synthesis [Figure 1]. [927]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 624 records were identified from 5 databases and 19 studies were included for final quantitative synthesis [Figure 1]. [927]…”
Section: Resultsmentioning
confidence: 99%
“…A total of 624 records were identified from 5 databases and 19 studies were included for final quantitative synthesis [Figure 1]. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Characteristics of the included studies Among the 19 studies in this meta-analysis, 122,003 patients undergoing CEA were included. All CEA procedures were performed after the year 2000, and studies were based on clinical registries, public medical databases, or single-center databases.…”
Section: Literature Search Processesmentioning
confidence: 99%
“…The comparable end points for SIE are even higher, and these include rates of combined stroke and death of 16.9% (95% CI, 9.2%-26.2%) and a combined rate of stroke, myocardial infarction, and death of 20.8% (95% CI, 13.2%-29.6%) . Only a few reports have studied outcomes of intervention in patients with cTIA (Table 2). Since patients with cTIA and SIE have similarly high risks of complication, they are usually combined into a single acute-syndrome group, and thus analysis of this subgroup of patients is challenging.…”
Section: Resultsmentioning
confidence: 99%
“…The authors concluded that postoperative complications after urgent CEA for cTIA are higher than expected after elective surgery but still acceptable, considering the natural history of patients with unstable neurologic symptoms . All of the studies from 1985 to 2018 reporting CEA in patients with cTIA have been summarized in Table 2. The wide range in practice patterns reflects patient heterogeneity and lack of standard selection criteria for intervention.…”
Section: Resultsmentioning
confidence: 99%
“…However, a dichotomy between symptomatic and asymptomatic patients is not accurate enough to precisely identify the risk of new symptoms or recurrences or to define the perioperative risk in patients submitted to carotid revascularization. As a matter of fact, the stratification of symptomatic patients according to the type of symptoms is important to identify those at higher risk of stroke and also to evaluate the risk of a revascularization procedure (1), since it is well known that patients with stroke in evolution or transient ischemic attack (TIA) in crescendo are more prone to perioperative complications compared with patients with a single stable TIA (2)(3)(4). Other than the clinical status, the presence and extension of cerebral ischemic lesions (CIL) is increasingly used as a stratification tool of these patients (5).…”
Section: Introductionmentioning
confidence: 99%